2023
DOI: 10.2337/dc23-0428
|View full text |Cite
|
Sign up to set email alerts
|

Association of COVID-19 and Development of Type 1 Diabetes: A Danish Nationwide Register Study

Abstract: OBJECTIVE To compare the incidence of type 1 diabetes (T1D) before and during the coronavirus disease 2019 (COVID-19) pandemic and determine whether severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is associated with T1D development. RESEARCH DESIGN AND METHODS All Danish residents age <30 years free of diabetes from 2015 to 2021 were included. Individuals were followed from 1 January 2015 or birth until th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…A registry study from Germany looking at 5127 children presenting with new‐onset diabetes in the COVID‐19 pandemic reported a similar association 2 . However, a nationwide study whilst reporting increases in new‐onset T1DM in the pandemic compared with previous years did not find this association 4 …”
Section: The Principal Outstanding Conundrum Is Whether Sars‐cov‐2 Is...mentioning
confidence: 95%
See 2 more Smart Citations
“…A registry study from Germany looking at 5127 children presenting with new‐onset diabetes in the COVID‐19 pandemic reported a similar association 2 . However, a nationwide study whilst reporting increases in new‐onset T1DM in the pandemic compared with previous years did not find this association 4 …”
Section: The Principal Outstanding Conundrum Is Whether Sars‐cov‐2 Is...mentioning
confidence: 95%
“…Type 1 diabetes mellitus (T1DM) is caused by the autoimmune destruction of β cells in the pancreatic islets and accounts for over 90% of childhood diabetes. A significant increase in new‐onset childhood T1DM has been reported in the COVID‐19 pandemic, 1–4 but the link with SARS‐CoV‐2 remains an enigma. This quandary is not unique to SARS‐CoV‐2.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the German study, the diagnosis of COVID‐19 in children was associated with an almost double increase in the incidence of T1D. In contrast, a Danish study found no significant association between SARS‐CoV‐2 infection and an increased risk of developing T1D 19–21 …”
Section: Introductionmentioning
confidence: 96%
“…In contrast, a Danish study found no significant association between SARS-CoV-2 infection and an increased risk of developing T1D. [19][20][21] Type 1 diabetes is an intricate autoimmune disease characterised by the destruction of insulin-producing cells by autoreactive immune cells. Environmental factors, such as viral infection, have the potential to initiate the destruction of insulin-producing beta cells.…”
Section: Introductionmentioning
confidence: 99%